Self-Assembling Nanovaccine Enhances Protective Efficacy Against CSFV in Pigs - Liu, Ze-Hui; Xu, Hui-Ling; Han, Guang-Wei; Tao, Li-Na; Lu, Ying; Zheng, Su-Ya; Fang, Wei-Huan; He, Fang (Frontiers in Immunology, 2021)
Classical swine fever virus (CSFV) is a highly contagious pathogen, which pose continuous threat to the swine industry. Though most attenuated vaccines are effective, they fail to serologically distinguish between infected and vaccinated animals, hindering CSFV eradication. Beneficially, nanoparticles (NPs)-based vaccines resemble natural viruses in size and antigen structure, and offer an alternative tool to circumvent these limitations. Using self-assembling NPs as multimerization platforms provides a safe and immunogenic tool against infectious diseases. This study presented a novel strategy to display CSFV E2 glycoprotein on the surface of genetically engineered self-assembling NPs. Eukaryotic E2-fused protein (SP-E2-mi3) could self-assemble into uniform NPs as indicated in Transmission electron microscope (TEM) and dynamic light scattering (DLS). SP-E2-mi3 NPs showed high stability at room temperature. This NP-based immunization resulted in enhanced antigen uptake and up-regulated production of immunostimulatory cytokines in antigen presenting cells (APCs). Moreover, the protective efficacy of SP-E2-mi3 NPs was evaluated in pigs. SP-E2-mi3 NPs significantly improved both humoral and cellular immunity, especially as indicated by the elevated CSFV-specific IFN-γ cellular immunity and >10-fold neutralizing antibodies as compared to monomeric E2. These observations were consistent to in vivo protection against CSFV lethal virus challenge in prime-boost immunization schedule. Further results revealed single dose of 10 μg of SP-E2-mi3 NPs provided considerable clinical protection against lethal virus challenge. In conclusion, these findings demonstrated that this NP-based technology has potential to enhance the potency of subunit vaccine, paving ways for nanovaccine development.